PRINSIP METODOLOGIS DALAM ILMU DAN KEISLAMAN : BAYANI, BURHANI, DAN IRFANI - Siregar, Winda Irsyidah Kholish; Muhammad Zalnur (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
This article explores the methodological foundations within Islamic scholarship through the bayani, burhani, and irfani approaches, which serve as three essential epistemological models for interpreting and advancing Islamic knowledge, aiming to clarify their distinct characteristics and evaluate their significance in contemporary academic contexts. The study adopts a library research method by reviewing and analyzing a wide range of classical and modern literature concerning Islamic epistemology. The results indicate that the bayani approach centers on textual authority and linguistic principles, the burhani approach emphasizes logical reasoning and rational justification, while the irfani approach highlights spiritual insight and inner experience; each model possesses its own strengths and limitations when applied independently but contributes to a more comprehensive understanding when used complementarily. The study concludes that these methodological principles enrich the intellectual heritage of Islamic sciences and offer a more coherent epistemological groundwork for developing integrative, contextually relevant, and responsive knowledge suited to present-day challenges.